Enhanced electrical properties of the polymorphic phase boundary on the tetragonal side in K0.48Na0.52NbO3-based lead-free piezoelectric ceramics. Issue 12 (15th June 2022) - Li, Min; Luo, Jin; Zhang, Tao; Liu, Yunfei; Lyu, Yinong
Abstract: Herein, (0.95− x )K0.48 Na0.52 NbO3 -0.05SrTiO3 - x CaZrO3 piezoelectric ceramics were prepared using a conventional solid sintering process, and their microstructures, phase structures, and ferroelectric, dielectric, and strain properties were studied. The crystal structure of the ceramics changed from the coexistence of an orthogonal–tetragonal phase on the orthogonal side at x  = 0 to that on the tetragonal side at x  = 0.02 by improving the orthogonal–tetragonal transition temperature (∼20 °C) with increasing CaZrO3 (abbreviated as CZ) doping. A high electric field–induced strain of 0.33% with a Curie temperature of T c  = 256 °C was obtained at x  = 0.02 and was approximately two times that observed at x  = 0. The dielectric constant and maximum polarization were the highest at x  = 0.02 in this (0.95− x )K0.48 Na0.52 NbO3 -0.05SrTiO3 - x CaZrO3 system. These materials would be promising lead-free ceramics in the future.